Ethics of human embryonic stem cell research: The perception of Buddhist, Hindu and Catholic representatives in Malaysia / Mathana Amaris Fiona Sivaraman - Mathana Amaris Fiona, Sivaraman (2016)
Human embryonic stem cell research (ESCR) raises ethical issues. Among the sources of embryonic stem cells are (i) embryos left from in vitro fertilisation (IVF) trials which are no longer needed for reproduction denoted as ‘surplus embryos’, and (ii) embryos intentionally created solely for research purposes from donated gametes via IVF, denoted as ‘research embryos’. The process of extracting stem cells from these 4–5 day old embryos which are subsequently destroyed in the research raises ethical controversies. Past studies on the ethics of ESCR largely revolve around the moral status of embryo, which is secular in nature. However, in a multi-religious and multi-cultural country like Malaysia, the ethical discussions pertaining to ESCR have taken a different outlook given the diverse views within and among the various faiths. The Malaysian Guidelines on Stem Cell Research and Therapy (2009) is based on the Islamic ruling (fatwa). Accordingly, surplus embryos are allowed to be used in research, but the creation of embryos solely for research purposes is prohibited. This study acknowledges the absence of documented views from other main religions like Buddhism, Hinduism and Catholicism pertaining to ESCR in Malaysia. In addition, no previous study has collected multiple religious viewpoints on the use of surplus and research embryos in ESCR. Hence, this study explores the ethical considerations of the religious leaders from the Buddhist, Hindu and Catholic traditions pertaining to ESCR in Malaysia, and their viewpoints on the use of surplus and research embryos. In this regard, the ethical standpoints of 11 religious leaders, comprising four Buddhist monks and leaders, four Hindu leaders and three Catholic priests were obtained via semi-structured, face-to-face iv interviews. The ethical responses of these participants are presented in reflection of various sacred texts. The main findings of this study is the emergence of three ethical concerns, denoted as themes, namely (i) sanctity of life, (ii) ‘do no harm’ and (ii) ‘intention’ of the research. Concerns on sanctity of life are directed at the religious notion of ensoulment and early consciousness, deliberating as to whether there is a sign of life in a 5-day old embryo. The precept ‘do no harm’ is closely related to the religious principle of ahimsa which prohibits hurting living entities. Finally, ‘intention’ of the research is viewed as a strong point among Buddhist and Hindu respondents to encourage ESCR. The findings indicate that generally, all Buddhist leaders approve the use of surplus and research embryos in ESCR except for one leader who disapproved the use of research embryos. The Hindu leaders cautiously support ESCR but it is limited to the use of surplus embryos. The Catholic leaders do not support any form of ESCR and strictly observe the inviolability of embryonic life. While the ethical concerns of the Catholic respondents are in accordance with the standpoint of the Vatican, the Buddhist and the Hindu respondents have provided new insights on the subject, striking new frontiers in the ethics discussion.